73 Parenting Experiences of Families of Refugee Background in the Greater Toronto Area: A Formative Study. (21st October 2022) - Ho, Bernice; Kaur, Pardeep; Kaukab, Tanvir; Rashid, Meb; Bowry, Ashna; Yousafzai, Aisha; Minhas, Ripudaman
Abstract: Background: As of date, the world is experiencing its highest levels of human displacement, with many families resettling in Canada. While there is an understanding that families of refugee background have complex, multigenerational mental health, and developmental needs, little is known about whether their parenting needs are met adequately in Canada after resettlement nor how COVID-19 related restrictions have further complicated their resettlement experience. Objectives: To gather data about the facilitators and barriers that impact the parenting experience of families of refugee background in the Greater Toronto Area (GTA) in the context of their children's unique developmental and resettlement needs. Design/Methods: This was a qualitative, community-based participatory research study. All data was collected from August 2019 to July 2020. In-depth interviews (IDIs) were conducted with caregivers of refugee background and healthcare providers that work closely with this population. Data were recorded, transcribed, and coded by two independent coders and a peer-debriefing strategy was used to verify the coding approach. Results: In total, 20 IDIs were conducted (7 caregivers, 13 care providers). Six key themes were identified: (1) Mental Health and Healthcare Access, (2) Language, (3) Navigating Canadian Systems, (4) Finances, (5) Cultural Dimensions of Caregiving, and (6) Advocacy and Agency. The caregivers and healthcare providers agreed that language is a migration barrier, housing and financial stability are challenging to obtain, and that families struggle to self-advocate. There was disagreement as to how families and healthcare providers viewed healthcare access: caregivers reported that they have good access, but the providers cited that there are still barriers, including health literacy and cultural differences. While caregivers believe they are well supported by the government, healthcare providers believe more funding and education on the families' rights are necessary. Finally, although most caregivers describe Canada as welcoming, healthcare providers highlighted more incidences of misunderstandings and gaps within the system that may allow families to fall through the cracks. Conclusion: Our study describes the unique facilitators and barriers to the resettlement, healthcare access, and lived experiences of families of refugee background raising children within the GTA.